Optimization of the fermentation of Bergenia sp. green leaves - Galambosi, B.; Galambosi, Zs.; Kosman, V. M.; Shikov, A. N.; Pozharitskaya, O. N.; Kauppinen, S.; Makarov, V. G. (Natural Resources Institute Finland, Luke, 2016)
The leaves of the commonly known decorative perennial, Bergenia species have several interesting biological activities. The green leaves contain arbutin up to 22 % (d.w.), a compound, which is used in cosmetic industry as a skin-whitening agent in humans. Tea prepared from the naturally fermented black leaves is used as beverage called Siberian tea or Mongolian tea in Russian ethno medicine. The fermented green leaves of Bergenia crassifolia are appearing to meet the criteria of being adaptogen. For the utilization of these new possibilities of Bergenia species during 2012–2014 several studies were carried out in SPECICROP project for elaborating a semi-industrial fermentation process of Bergenia leaf yield. The experiments were carried out in MTT Agrifood Research Finland Mikkeli with cooperation of St.-Petersburg Institute of Pharmacy, St-Petersburg, Russia. On the base of these experiments we elaborated the optimized parameters of the fermentation process and described a technological recommendation suitable for small size farm entrepreneurs.
Appendix 1. Recommendation for the fermentation process of Bergenia leaf yield
Keywords: Bergenia; fermentointimenetelmä; arbutin content; fermentation parameters; technological recommendation; arbutiini; menetelmät; fermentointi